Effectivity of the Microsoft Excel Application on Student Understanding in Statistics Courses - Simaremare, Sinta; Siregar, Rosma (Indonesian Journal of Education and Social Humanities, 2024)
This research aims to test the effectiveness of the Microsoft Excel application on students' understanding of statistics courses. This research is quantitative research and descriptive data analysis, aimed at measuring students' level of understanding of various statistical concepts. Because research data is in the form of numbers, while descriptive analysis is statistics which functions to provide an overview of the object being studied. In this research, researchers used a total sampling technique where the entire population was sampled. So a sample of 22 people was obtained. For data collection, researchers used an online questionnaire method using Google form, the data obtained was analyzed using descriptive analysis. Of the 25 participants, 22 students answered the questionnaire. Respondents' answers regarding question 1, How often do students use Microsoft Excel (P1), Students who said they used Microsoft Excel several times a week and students who said they used Microsoft Excel once a month had the same percentage, namely 31.8%. Then 9.1% said they rarely use Microsoft Excel. Several things that can be concluded from this research are that it is still found that some students do not understand how to use Microsoft Excel, so there is a need for training for students to introduce and train students in the Regular B Building Engineering Education Study Program more deeply in applying Microsoft Excel in solving problems and processing data. and make it easier to complete assignments in statistics courses.